Anonymous

# Prove the following identity algrebraically: 1-(sinx)(cosx)(tanx)= (cos^2)x?

Prove the following identity algrebraically: 1-(sinx)(cosx)(tanx)= (cos^2)x

### 4 Answers

Relevance

- Anonymous9 years agoFavorite Answer
substitute

tanx=sinx/cosx and

1-sin^2 x = cos^2 x

- Login to reply the answers

- peabodyLv 79 years ago
LHS

= 1-(sinx)(cosx)(tanx)

= 1 - sinx * cos x * sin x / cos x

= 1- sin^2 x

= cos^2 x

= RHS

- Login to reply the answers

- 4 years ago
convey tanx =sin x/cos x , and look on the id for sin 2x (or cos 2x. convey, you'll see which one to apply!) i need to handbook you to the answer, not provide it to you. that is extra effective!

- Login to reply the answers

- TCLv 79 years ago
1 -( sin)(cos)(tan) = cos^2

1 - (sin)(cos)(sin/cos) = cos^2

1 - (sin)(sin) = cos^2

1 - sin^2 = cos^2

cos^2 = cos^2

- Login to reply the answers

Still have questions? Get your answers by asking now.